Report on management of public enterprises in the Caribbean (CARICAD BB, 1992)
Presents two studies. The first of which looks at the rationale of public enterprises in the English-speaking Caribbean. Proposes an analytical framework for the study of Caribbean public enterprise and makes a critique of public enterprise operations in the Caribbean. The second study reviews emerging public policy issues in respect of the management and reforms of the public sector in the region. Touches on the role that the Caribbean Centre for Development Administration (CARICAD) can play in ongoing reforms.
DC